Toward IP converged heterogeneous mobility: A network controlled approach - Melia, Telemaco (2007)
Envisioning a future where mobile terminals equipped with one or more network devices are able to roam across wireless or wired networks, in a diverse macro and micro wireless cells environment, requires the development of enhanced methods to control IP-based mobility. These methods should consider traditional terminal mobility (mainly due to user movement) as well as mobility across heterogeneous networks in the presence of semi-static users. For this to become reality, a cross layer interaction is required starting from a potentially large diversity of layer two access technologies up to the common IP layer, allowing the exchange of messages between terminals and network components. Furthermore, traditional host mobility driven concepts need to evolve, and include more stringent mobile operator requirements in context of fully driven network controlled mobility. This paper presents and evaluates a novel framework design, based on the IEEE 802.21 future standard, encompassing network driven as well as host driven mobility. This paper evaluates signalling aspects, algorithm design and performance issues.